THE STRATEGY OF INCREASING QUALITY OF PRODUCTION, AND MARKETING SERVICES WITH METHODS OF QFD (QUALITY FUNCTION DEPLOYMENT) - Fiernaningsih, Nilawati; Herijanto, Puji (International Journal of Psychosocial Rehabilitation, 2020)
Photography as one of the areas of concern in Indonesia, creative industries subsector is part of Film, Video, and photography, among 15 subsector which is handled by the Kemenparekraf at this time. Photography as part of the creative industries Indonesia is an industry that encourages the use of the creativity of the individual Quality Function Deployment (QFD) is a method of planning structure the product and its development, which allow a development team explains specifications of the desires and needs of consumers, which then evaluate any proposed product or service capabilities that systematic , there is the eight dimensions of quality are: (1) performance (performance); (2) the privilege (features); (3) reliability (reliability); (4) conformity (conformance); (5) endurance (long- term durability); (6) the ability of service (service ability); (7) beauty (estetic); (8)